Praktik Strategi Guru dalam Pembelajaran Membaca Berbasis Media Gambar dan Diferensiasi Pembelajaran di Sekolah Dasar Islam - Ilmawati; Kusairi; Robby Jundi Lestari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study is motivated by initial classroom observations in Grade III at SD IT Ihya As-Sunnah Singkut, which revealed that some students experienced reading difficulties, low learning motivation, and an underdeveloped sustainable reading habit. Of the 14 students, seven were not yet fluent readers, which affected their comprehension of learning materials. This qualitative study employed in-depth interviews, classroom observations, and student questionnaires for data collection. The findings indicate that the implementation of student-centered teaching strategies, differentiated instruction based on students’ reading abilities, and the use of picture-based media as instructional scaffolding enhanced students’ engagement, reading interest, and comprehension. The study concludes that integrating student-centered approaches, differentiated instruction, and visual media is effective in supporting early reading instruction and highlights the importance of collaboration among teachers, schools, and parents in fostering students’ literacy development.